De novo formation of phthalimide from ubiquitous phthalic acid derivatives during the drying process of tea (Camellia sinensis) and selected herbal infusions. (16th April 2022) - Wittig, Maximilian; Biller, Julia; Nitsopoulos, Athanasios; Friedle, Albrecht
Highlights: Plants were grown under shielded conditions to exclude any presence of folpet. Phthalimide contents were determined and compared by GC–MS/MS and LC-APCI-MS/MS. In all plants analyzed phthalic anhydride was observed as a relevant background load. Phthalimide can be formed in relevant quantities even in the absence of folpet. Phthalimide formation under heat correlates with occurrence of phthalic anhydride. Abstract: It is well documented that under some circumstances phthalimide, a known degradation product of the fungicide folpet, can be formed as an artifact during gas chromatographic analysis. This fact explains one phthalimide source, but does not explain a great number of positive findings in the group of dried plant commodities obtained with an artifact-free analysis. Therefore, in the framework of this study, herbal and tea plants were grown in a glasshouse under the best possible protection against external environmental influences and ensuring the exclusion of the use of folpet. It was demonstrated that relevant amounts of phthalimide are formed during the drying process as part of the routine production of tea and herbals and in the absence of folpet. In this context, the presence of the widespread environmental chemical phthalic anhydride and its impact was investigated. We conclude that phthalimide is no reliable indicator for the active use of folpet.